2022
DOI: 10.1007/s10461-022-03717-2
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of a Remote Coaching mHealth Adherence Intervention in Youth Living with HIV

Abstract: Youth living with HIV (YLWH) in the US have low rates of viral suppression (VS). In a prospective randomized clinical trial (ATN152) that enrolled 89 YLWH on antiretroviral therapy (ART) with detectable viral load, we evaluated a 12 week triggered escalating real-time adherence (TERA) intervention with remote coaching, electronic dose monitoring (EDM), and outreach for missed/delayed doses compared to standard of care (SOC). Median [Q1, Q3] percent days with EDM opening was higher in TERA (72% (47%, 89%)) vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This researcher differentiated the intervention group with virtual group counseling via the Telegram application. (13) The other nine studies provided intervention with some media, such as the mHealth platform (10, [15][16][17], virtual counseling (18), digital media application (19,20), computer-based implementation (21), and cellular phones. (19) The researchers summarized the medicine consumption adherence with CD4 and virtual load checkup (10, [15][16][17][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This researcher differentiated the intervention group with virtual group counseling via the Telegram application. (13) The other nine studies provided intervention with some media, such as the mHealth platform (10, [15][16][17], virtual counseling (18), digital media application (19,20), computer-based implementation (21), and cellular phones. (19) The researchers summarized the medicine consumption adherence with CD4 and virtual load checkup (10, [15][16][17][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…(13) The other nine studies provided intervention with some media, such as the mHealth platform (10, [15][16][17], virtual counseling (18), digital media application (19,20), computer-based implementation (21), and cellular phones. (19) The researchers summarized the medicine consumption adherence with CD4 and virtual load checkup (10, [15][16][17][19][20][21]. The researchers also found a technique to measure the patients' adherence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the original plan was to use all 48 weeks of EDM data, after 24 weeks on study, increasing numbers of participants in both arms (13 of 43 SOC participants and 11 of 42 TERA participants, see Figure S1, Supplemental Digital Content, http://links.lww.com/QAI/B990) had discontinued use, as indicated by increasing proportions of participants with a complete absence of opening events and no association between EDM events and viral suppression. 14 For this reason, the analysis plan was updated to focus on the intervention period and the 12 weeks postintervention. We included follow-up until the last time the bottle was opened, after which we assumed the participant had stopped using the device.…”
Section: Methodsmentioning
confidence: 99%
“…The primary analysis of the study reported a positive effect of the intervention on EDM-based adherence during the 12-week intervention phase of the study and the 12 weeks after the intervention, but no association of the intervention with percent of participants with suppressed viral load (HIV-1 RNA <200 or <50 copies/mL) throughout follow-up. 14 These analyses used EDM-based adherence aggregated over each 12-week period.…”
Section: Introductionmentioning
confidence: 99%